The Culture of the Moi Kelim Indigenous People in Malaumkarta: Development theory and Energy Self-Reliance - Ramaldy Krisna Indradipradana; Rafi Sanjaya; Rezya Agnesica Helena Sihaloho (Komunitas : Jurnal Pengabdian Kepada Masyarakat, 2023)
Energy is an important sector in development because it can be the main driving tool in the transformation of an agrarian civilization to an industrial civilization. Energy also plays a significant role in the development of the Moi Kelim indigenous people in Malaumkarta and has a positive impact on achieving energy independence for the Moi Kelim indigenous people. This article examines the relationship between development theory and energy independence in the Moi Kelim indigenous people in Malaumkarta, where the Moi Kelim indigenous people preserve culture and local wisdom values to achieve energy independence. Egek is a local wisdom of the Moi Kelim indigenous people which results in limited resource utilization in Malaumkarta. Thus, the Moi Kelim indigenous people can utilize resources while maintaining the environment in Malaumkarta. Also, in their daily practice, the Moi Kelim people are still able to accept technological developments. Therefore, a study needs to be conducted to analyze the development in Malaumkarta by the Moi Kelim indigenous people in achieving energy independence from a development theory perspective. This study uses a qualitative method using development theory from Todaro & Smith (2015). The results of this study are that the Moi Kelim indigenous people have fulfilled the objectives of development theory. Thus, the indigenous people of Moi Kelim can become an example for other indigenous peoples in achieving energy independence.